PENGARUH PENGEMBANGAN KARIER, KEADILAN KOMPENSASI, DAN BEBAN KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN KLINIK NAJWA MEDIKA DEPOK - Arini Estetia Putri; Nining Handayani; Rizki Adriansyah Rubini (Journal of Innovation Research and Knowledge, 2025)
Turnover intention is a crucial issue in human resource management. Studies on turnover intention in healthcare facilities are still rare. This study aims to analyze the effects of career development, compensation fairness, and workload on turnover intention. This research design is quantitative research. Data were obtained from questionnaires of 38 respondents and the data were analyzed using multiple linear regression test SPSS version 21. The results of this study indicate that career development does not affect turnover intention, compensation fairness has a significant negative effect on turnover intention, and workload has a significant positive effect on turnover intention. Simultaneously, career development, compensation fairness, and workload have a significant effect on turnover intention. Conclusion: 1. Career development does not affect turnover intention. 2. Compensation equity has a significant negative effect on turnover intention. 3. Workload has a significant effect on turnover intention. 4. Career development, compensation equity, and workload simultaneously affect turnover intention